Bioactive feed additives in animal nutrition: bridging innovation, health, and sustainability - Buonaiuto, Giovanni; Danese, Tommaso; El-Sabrout, Karim; Yıldırım, Arda (Frontiers in Veterinary Science, 2025)
Animal nutrition is shifting the focus from simply providing animals with feed to the nutrition of the whole system, balancing health, welfare, and ecological attention. This perspective synthesizes recent developments on bioactive feed additives (including phytogenic compounds, probiotics, prebiotics and synbiotics, exogenous enzymes, organic acid, and emerging options such as algal extracts, bioactive peptides, and fermented substrates) and evaluates their contributions to sustainable production. The aim of this paper is to outline how these interventions can enhance digestive efficiency, gut integrity, immune competence, and resilience to stress, thereby working with the aim to reduce antibiotic use, improve feed conversion, lower emissions, and valorization of agro-industrial by-products within circular economy schemes. Furthermore, appraising persistent bottlenecks will be covered, such as: heterogeneous responses across species and production contexts, narrow dose–response windows and interactions among multiple actives, limited evidence on long-term safety and carry-over into edible products, and fragmented regulatory pathways. Finally, a forward agenda will be proposed, which leverages multi-omics to elucidate host–microbe–diet mechanisms and define biomarkers of response; applies precision feeding and digital monitoring to individualize dosing; designs multifunctional formulations with complementary modes of action; and embeds One Health and life-cycle assessment to balance efficacy, safety, and sustainability. Reframed as strategic tools rather than ancillary supplements, bioactives can help build resilient, resource-efficient animal production systems.